2012
DOI: 10.1002/anie.201200057
|View full text |Cite
|
Sign up to set email alerts
|

Material Transfer and Polarity Reversal in Contact Charging

Abstract: In touch: the outcome of contact electrification between dielectrics depends not only on the transfer of charge but also on the transfer of material. Although only minute quantities of materials are being exchanged during contact, they can reverse the polarity of dielectrics. The reported results corroborate the mosaic model and suggest that the observations are because of the mechanical softness/hardness of the materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 44 publications
5
139
0
1
Order By: Relevance
“…4(a) is in according with the results observed by Baytekin et al, 35 where it was found that the contact induced charge got saturated as the contact duration increased. In fact, although the contact processes in the experiment of Baytekin et al 35 is more complex than the ones in our experiment, the two contact processes may have analogy, which we think is worthy of further studying.…”
Section: Contact Electrification Modeling and Discussionsupporting
confidence: 91%
“…4(a) is in according with the results observed by Baytekin et al, 35 where it was found that the contact induced charge got saturated as the contact duration increased. In fact, although the contact processes in the experiment of Baytekin et al 35 is more complex than the ones in our experiment, the two contact processes may have analogy, which we think is worthy of further studying.…”
Section: Contact Electrification Modeling and Discussionsupporting
confidence: 91%
“…Here we stress again that the temporal bipolar contact charging can only be observed, if there is such a spatial bipolar charging. During separation, positive and negative charges are generated again as a result of further bond-breakages (as also supported by a detectable amount of material transfer that occurs between the surfaces) 11 . These initiate the subsequent electron flow from/to the electrodes, which are detected as signals 7 and 8.…”
Section: Resultsmentioning
confidence: 90%
“…CE depends on contacting material’s physical and chemical properties, environmental conditions and the nature of the physical contact between materials, and therefore ambiguous results are encountered in the related literature, hampering the uncovering of its mechanism 9,10 . The event gets even more complicated when mass transfer (exchange of bits of charged material between contacting surfaces) is involved 11,12 . Recent discoveries made by using chemical and surface analysis techniques, however, provided a large step-forward in contact electrification research, for instance; (1) charging of two identical surfaces questioned the idea of pure electron transfer mechanism and undermined the concept of building up of a general triboelectric series 1316 (2) the observation of nano-to-macro oppositely-charged charge domains on surfaces 1725 disproved the previously assumed homogenous charge distribution on surfaces after contact, (3) the measurement of charges in nano domains showed that the electric potential on surfaces is ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our fresh PDMS-based TENG generated a stable voltage and current without a charging step. Given the extended curing time of our PDMS films, we think that material transfer may not occur from the PDMS film to the ITO surface during the contact/separation operations [19,20]. Thus, the resulting triboelectric signal could be weak without requiring a charging step.…”
Section: Resultsmentioning
confidence: 97%